PENGEMBANGAN USAHA PRODUKSI TIKUS PUTIH (Rattus norvegicus) TERSERTIFIKAS DALAM UPAYA MEMENUHI KEBUTUHAN HEWAN LABORATORIUM - Widiartini, Wiwik; Siswati, Eka; Setiyawati, Ana; Rohmah, Ita Miftahur; Prastyo, Eko (Program Kreativitas Mahasiswa - Kewirausahaan, 2013)
The purpose of program is learning about breeding of rats, produce certified rats, meet a demand for animal laboratory and enhance entrepreneurial spirit of students. The method used is survey market, rearing of rats, breeding and recording, promotion and marketing, finally bussiness evaluation. Results showed rearing of rats has done according to standard operational procedure, prepared by a team of âDIPOKOeSâ guide by adviser. Recording has done continously. Promotions have done to university and colleges around Semarang. Mass marketing will start in September 2013. The next target will prepare research cage for rent and design of cage aircrafting.Â Keywords: certified rats, breeding, laboratory.